Effect of different types of liquid natural rubbers on the modification of DGEBA-based epoxy resin - Ly, Pham Huu; Thanh, Do Bich; Son, Pham Tung; Giang, Le Duc (Vietnam Journal of Science and Technology, 2015)
Diglycidyl ether of bisphenol A (DGEBA)-based epoxy and varying content of hydroxyl terminated liquid natural rubber (HTNR) or carboxyl-terminated liquid natural rubber (CTNR) were cured using an aromatic amine hardener. The ultimate aim of the study was to modify the brittle epoxy matrix by liquid rubber to improve the toughness characteristics. Tensile, flexural, and fracture toughness behaviors of neat as well as modified networks have been studied to observe the effect of different types of liquid natural rubber modification. The morphological evolution of the toughened networks was examined by scanning electron microscope (SEM), and the observations were used effectively to explain the impact properties of the network having varying content of liquid natural rubbers. The results showed that the impact resistance of both HTNR-modified DGEBA and CTNR-modified DGEBA was superior to that of the pure epoxy resin, among which the impact resistance of CTNR-modified DGEBA was better than that of HTNR-modified DGEBA. For all the composites with HTNR or CTNR, the impact resistance increased with elastomer concentration up to 15.0 parts per hundred parts of resin (phr). Higher concentration of the elastomers resulted in larger particles and gave lower impact values. These results allow the conclusion that 15 phr is the maximum content of HTPB or CTNR that might be added in DGEBA composites for a positive effect upon the impact strength.